Analysis of the development trend of Chinese seafood imports from Southeast Asia after the Fukushima-Daiichi radioactive treated water discharge from Japan - Xiaojun Qi; Liguo Gao (PLoS ONE, 2025)
Japan’s decision to discharge the Fukushima-Daiichi radioactive treated water into the Pacific Ocean has drawn widespread international concern regarding radioactive contamination of seafood and its impact on the marine ecosystem and human health. China’s seafood import trade is confronted with a potentially significant threat. In the favorable circumstances created by China’s suspension of seafood imports from Japan, This article analyzes the impact of Japan’s radioactive treated water discharge on seafood safety and human health, as well as the importance of the Chinese market in the international trade of seafood, and analyzes the seafood export data from Southeast Asian countries to China from 2018 to 2024. A significant increase in seafood exports from countries such as Indonesia, Myanmar, and the Philippines to China was observed. Conversely, there has been a notable decline in the export volumes from Vietnam and Thailand. This paper proposes some proactive strategies for Southeast Asian seafood exports to China, including actively familiarizing with China’s import regulations and standards, optimizing export strategies, cultivating a positive and favorable product image, aligning with the needs of Chinese enterprises, and ensuring food safety.